Risk of Invasive Pneumococcal Disease in Children with Sickle Cell Disease in England: A National Observational Cohort Study, 2010–2015. Issue 7 (27th December 2017) - Oligbu, Godwin; Collins, Sarah; Sheppard, Carmen; Fry, Norman; Dick, Moira; Streetly, Allison; Ladhani, Shamez
Abstract : Objective: To describe the clinical presentation, risk factors, serotype distribution and outcomes of invasive pneumococcal disease (IPD) in children with sickle cell disease (SCD) following the introduction of the 13-valent pneumococcal conjugate vaccine (PCV13) in the UK. Design: Prospective national newborn screening for SCD and enhanced national IPD surveillance. Participants: Children with SCD born in England between 1 September 2010 and 31 August 2014 who developed laboratory-confirmed IPD by 31 December 2015. Main outcomes and measures: Risk of IPD in children with SCD compared with children without SCD during the surveillance period. Results: Eleven children homozygote for haemoglobin S (HbSS) and one double heterozygote for haemoglobin S and C (HbSC) developed IPD. Septicaemia (n=7) and lower respiratory tract infection (n=4) were the main clinical presentations, and serogroup 15 (not present in PCV13) was responsible for 73% (8/11) of cases. Three children with HbSS (27%) died compared with <5% nationally. Children with HbSS had a 49-fold (95% CI 27 to 89, P<0.001) higher risk of IPD compared with their peers without SCD. Conclusions: Children with SCD remain at increased risk of IPD despite national newborn screening, early penicillin prophylaxis and high pneumococcal vaccine uptake. They are also more likely to die of their infection compared with their peers without SCD. Most IPD cases are now due to serotypes not covered by PCV13. Healthcare professionals need to work more closely with families with SCD and local communities to emphasise the importance of penicillin prophylaxis, explore barriers, allay misguided beliefs and facilitate rapid access to healthcare.